Development of preschool social emotional inventory for preschoolers: a preliminary study - Goh Wah Im; Yeo Kee Jiar; Rohaya Bt. Talib (Institute of Advanced Engineering and Science, 2019)
Social-emotional competencies have been established as important predictors in children’s mental health, school readiness and academic success. Age and developmentally appropriate screening for preschool children is important for early detection of developmental delays and early intervention. The purpose of this study is to measure preschool children’s social emotional competencies (SEC) based on the Malaysian context using the Preschool Social Emotional Competency Inventory (P-SECI) developed to provide parents, teachers and childcare professionals with a standardized, norm-referenced, reliable and valid instrument. A pool of 50 items were created for P-SECI, representing eight clusters of social emotional competencies in children: self-awareness, social awareness, self-management, relationship management, attachment, communication, responsible decision making and pro-social skills. This pilot study involved two public Annex preschools in Johor Bahru, purposely selected with 49 preschool children as respondents. Results showed that P-SECI has a high reliability index (Alpha Cronbach-Teachers .98 and Parents .95). Initial findings also showed that Teachers and Parents differ in their evaluation of their children’s SEC according to age and gender. But for the age criteria, the mean difference is slightly wider in comparison to gender. Therefore, P-SECI is relevant in predicting children’s mental health, school readiness and academic achievement. Results from the study also showed that the inventory holds promise as a reliable and valid instrument to evaluate SEC in young children according to the Malaysian context.